Growth, feeding and sex change in the sequential protandric shrimp Nauticaris marionis Bate 1888 at the Prince Edward Islands (Southern Ocean) - Vumazonke, Lukhanyiso Unam (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2005)
Demographic parameters and the general biology of the subantarctic shrimp Nauticaris marionis from the Prince Edward Islands were investigated. The carapace length is the most accurate indicator of body size and it was confirmed that N. marionis is a partially protandric hermaphrodite. Gravid females of N. marionis observed mainly in March with negligible hatching persisting until April/May. The majority of juveniles develop into males. Juveniles are characterised by an appendage on the endopodite of the first pleopod called the appendix interna or a.i.1. Juveniles that develop into males do so by growing a further appendage on the endopodite of the second pleopod. This appendage characterises males and is called the appendix masculina (or a.m.). Juveniles may develop directly into primary females through the development of an ovary and the loss of the a.i.1. The sequence differs among individuals, with some developing the ovary before losing the a.i.1 and others losing the a.i.1 first. Loss of the a.i.1 appears to be by shedding during a single moult, rather than by atrophy. Females can also develop by an alternative route as secondary females. Such animals first become males with an a.m. and then develop an ovary, thus forming an intermediate form called a tertium quid, or "third thing" . Again, there are two forms of tertium quid. Tertia quae a have the a.m. as well as the a.i.1. Tertia quae b have the a.m. in combination with an ovary but no a.i.1. Either form of tertium quid can develop into a secondary female through loss of the a.m., and in the case of the tertium quid a, loss of the a.i.1. It is unclear whether sexual differentiation occurs in the plankton or just after N. marionis settles on the benthos. The results of gut content analysis suggest that N. marionis is an opportunistic feeder, preying on a variety of prey with a preference for detritus, benthic amphipods and gastropods. Cannibalism of conspecific pleopods by large individuals of N. marionis occurred mostly in females, particularly in incubation containers. Cannibalism also occurs in males, and its occurrence depends on individual size, not gender. No diel patterns were observed in the feeding activity of N. marionis. In situ daily rations of males (carapace length <7mm) and females (>7mm) were equivalent to ≈10% and ≈5% of body dry weight, respectively. The von Bertalanffy growth curve parameters were empirically identified, by cohort analysis of data collected during 4 years, as K = 0.22239/year, L[subscript]∞ = 14.05789mm, t₀ = -0.05174, L₀ = 0.16083mm. N. marionis can survive up to seven years under natural conditions.
Keywords: Shrimps -- Prince Edward Islands; Shrimps -- Feeding and feeds; Shrimps -- Nutrition; Shrimps -- Growth